Oxydative desulfuration of [14C]-fenitrothion by liver microsomes of some species of fishes [Oksidasi desulfurasi [14C]-fenitrothion pada mikrosom liver dari beberapa spesies ikan] - Djamartumpal F. Lumban Batu (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2011)
A study was made of the oxydative desulfuration of [14C]-fenitrothion by liver microsomes of some species of fishes. The preliminary research had been carried out to obtain the optimal condition of fenitrothion assay of the liver microsomes of every test spesies, including : pH, temperature, pre incubation time, incubation time, trypsin inhibitor, NADH and NADPH effect. The hepatic microsomes of treated and control were subjected to fenitrothion oxydative desulfuration assay, protein and cytochrome P-450 content and another enzyme activities. AbstrakSuatu studi telah dilakukan tentang oksidasi desulfurasi dari [14C]-fenitrothion yang berlangsung pada mikrosom liver dari beberapa spesies ikan. Penelitian pendahuluan telah dilakukan untuk mengetahui kondisi optimum pada suatu uji fenitrothion yang berlangsung pada liver dari spesies uji meliputi beberapa parameter seperti: pH, suhu, waktu pra-inkubasi, waktu inkubasi, inhibitor tripsin, serta pengaruh dari NADH dan NADPH. Mikrosom liver dari kontrol dan perlakuan telah digunakan pada uji oksidasi desulfurasi fenitrothion untik mendeterminasi kandungan protein dan sitokrom P-450.